2013
DOI: 10.1016/j.jad.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of personality disorders in anxiety disorders: A meta-analysis of 30 years of research

Abstract: Background. A comprehensive meta-analysis to identify the proportions of comorbid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(120 citation statements)
references
References 200 publications
5
105
0
10
Order By: Relevance
“…The association may be understood in part with reference to broader literature concerning personality disorder, anxiety and depression, as well as other work showing that personality disorder is a risk factor for poor future mental health (Moran et al, 2016). High comorbidities between personality disorder and anxiety (Friborg et al, 2013) and depression (Friborg et al, 2014) are well documented, and coexisting personality disorder has been linked to poorer outcomes in anxiety (Ansell et al, 2011) and depression (Grilo et al, 2010). Our finding of an attenuated association between personality disorder and antenatal depressive symptoms with the adjustment for preconception background factors including common mental disorder does not negate the possibility of an independent association between personality disorder and antenatal depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association may be understood in part with reference to broader literature concerning personality disorder, anxiety and depression, as well as other work showing that personality disorder is a risk factor for poor future mental health (Moran et al, 2016). High comorbidities between personality disorder and anxiety (Friborg et al, 2013) and depression (Friborg et al, 2014) are well documented, and coexisting personality disorder has been linked to poorer outcomes in anxiety (Ansell et al, 2011) and depression (Grilo et al, 2010). Our finding of an attenuated association between personality disorder and antenatal depressive symptoms with the adjustment for preconception background factors including common mental disorder does not negate the possibility of an independent association between personality disorder and antenatal depression.…”
Section: Discussionmentioning
confidence: 99%
“…They are associated with functional impairments that can persist even when diagnostic thresholds are no longer met (Skodol et al, 2005) and are linked to premature mortality (Fok et al, 2012). Rates of comorbid anxiety (Friborg et al, 2013) and depression (Friborg et al, 2014) are high in personality disorder, and comorbid personality disorder predicts poorer outcomes for these disorders (Ansell et al, 2011;Newton-Howes et al, 2014). Furthermore, our group has recently shown that the presence of personality disorder in young adulthood independently predicts future anxiety and depression over a decade later (Moran et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, although models explaining it include pre-existing factors, such as personality disorder (Friborg et al 2012 ) and biological and cognitive factors (Bomyea et al 2012 ), a diatheses-stress model involving stressors including the event at hand appears to help explain it.…”
Section: Commentmentioning
confidence: 99%
“…Esta condición se vincularía a los niveles de exigencia académica propios de las carreras de salud, factores socioeconómicos y socioemocionales 10,11 , además de variables como el tipo de carrera, el sexo 4 , y ser alumno/a de primer año en la carrera 11 . Un aspecto a considerar en cuanto a la emergencia de estos cuadros, es la relación de ellos con la personalidad de los estudiantes de la salud [12][13][14][15][16] . En la actualidad los estudios que vinculan estas variables, son escasos y toman como referencia teórica el modelo de los cinco grandes factores 17 .…”
Section: Introductionunclassified